Less Than a Moment: Posadas County Mystery #14 - Havill, Steven (Naperville, Illinois : Poisoned Pen Press, 2020)
"A Posadas County Sheriff's Department Dispatcher sticks a Post-It note on an incident report. What he meant to write was, "Not for news," hoping that the newspaper reporter who drops into the Sheriff's Office each morning would ignore the report. But what he unintentionally wrote was, "Note for news," and so the arrest of Quentin Torrez, nephew of Posadas Sheriff Robert Torrez, goes public. And Quentin, who has applied for a job with the NightZone excursion narrow gauge railroad, loses any chance at employment. Shortly thereafter, a night-time drive-by shooting riddles the front of the newspaper office - and despite the late hour, two of the newspaper employees are inside, and both are wounded. Are the incidents connected? Sheriff Torrez and Undersheriff Estelle Reyes-Guzman will need all the help they can get to solve this puzzling case"--Provided by publisher.
Posadas County, New Mexico has enjoyed a surge in visitors, jobs, and prosperity since rancher Miles Waddell used much of his inherited half billion to create an internationally renowned astronomy complex atop Torrance Mesa. Benefits include a narrow gauge train linking the village of Posadas to NightZone. When speculator Kyle Thompson and his wife quietly purchase a large scrubby acreage to the north of NightZone. any light pollution would jeopardize the astronomy complex. When a drive-by shoot-up at the Posadas Register wounds a reporter and the paper's editor, Sheriff Bob Torrez and Undersheriff Estelle Reyes-Guzman see a connection to NightZone... and worse, a connection with Torrez's own nephew. -- adapted from back cover
new book winter 2024.
Keywords: Sheriffs -- Fiction; Policewomen -- Fiction; Murder -- Investigation -- Fiction; Truthfulness and falsehood -- Fiction; Truthfulness and falsehood; Murder -- Investigation; Policewomen; Sheriffs; New Mexico -- Fiction; New Mexico; Detective and mystery stories; Detective and mystery fiction; Fiction; Detective fiction; Mystery fiction